Steam Boiler System / Mohamad Aizudin Mohd Yusuf, Ishak Mohd Yusof and Mohamad Zakuwan Abd Wahab - Mohd Yusuf, Mohamad Aizudin; Mohd Yusof, Ishak; Abd Wahab, Mohamad Zakuwan (2005)
Steam Boiler System is a design as a thesis that purpose to complete our diploma course in this final year. We choose this project because want to study about the boiler for our next experiment. The purpose of this project is to fabricate a simple of steam boiler system and study how the different types of blade effect the system. In this case, we are trying to show a model that consists of some simple components. We also need to prove that the system is work successfully. This is involving some calculation that we need to determine the pressure and efficiency between two different blades. The system is simple no need to use the complicated component. The budget we expenses for this project is about RM 118.70.The budget is including the components , process brazing,making blade and other expenses.